Paper 60: Objective Diagnosis of Multidirectional Instability in Adolescent Patients Based on Glenohumeral Joint Capsule Dimensions on MR Analysis. Issue 7 (30th July 2022) - Yoder, Mason; Veerkamp, Matthew; McDonald, Colin; Parikh, Shital
Objectives: Multidirectional Instability (MDI) of shoulder in adolescents is a clinical diagnosis and there are no defined objective criteria to validate the diagnosis. Most patients with MDI have no identifiable labral or capsular tear pattern on MR imaging. The objective of this study was to identify objective criteria for MDI diagnosis based on rotator interval and glenohumeral capsular dimensions on MR imaging in surgically confirmed adolescents with MDI. Methods: In a comparative retrospective study, the clinical records and MR arthrogram of adolescent patients treated for shoulder instability at our center between 2008 and 2019 were reviewed. Twenty-four adolescents with surgically confirmed MDI were age-matched to 25 control patients. The width and depth of the rotator interval and multiple linear dimensions of the glenohumeral capsule were measured on sagittal-oblique MR arthrography sequences, after controlling for glenoid size (Fig 1). The measurements that differed significantly were identified using unpaired t-tests. These values were plotted on receiver operator characteristic (ROC) curves, which were used to determine threshold values for identifying MDI. Power analysis showed a sample size of 16 in each group to be sufficient to detect 5 mm difference in average capsular dimension of 20 mm (power 0.8) Results: 24 patients (28 shoulders) 20 females, 4 males were in the MDI group; average age at time of surgery was 15.2 years (range, 8-20 yrs). The control group consisted of 25 patients (27 shoulders), 9 females, 16 males; average age was 15.4 years (range, 11-18 yrs). Rotator interval depth was significantly greater in the MDI group vs control (MDI 8.5mm; Control 6.1mm) (p <0.01), as were the inferior, posteroinferior, and posterior dimensions of the glenohumeral joint capsule (24.5 vs 20.4mm, 26.4 vs 21.9mm, and 22.5 vs 19.3mm, respectively; p <0.01) (Table 1). Rotator interval width and anterior capsular dimensions were not significantly different between groups. The ROC-derived threshold values for identifying MDI using MR arthrography were Rotator interval depth = 7.4mm; Posterior capsule = 20.9mm; Inferior capsule = 22.4mm; Posteroinferior capsule = 24.0mm. Conclusions: Rotator interval depth and dimensions of glenohumeral joint capsule in the inferior, posterior and posteroinferior quadrant on MR arthrography were significantly greater in adolescent patients with MDI. Measurement of rotator interval depth and glenohumeral capsular dimensions on MR arthrography can be used to supplement clinical diagnosis of MDI. Table 1. Glenohumeral joint capsule measurements (* statistically significant)